The Itinerant Economist : Memoirs of a Dismal Scientist. - Jones, Russell (London Publishing Partnership, 2014)
Economists and bankers have long been much maligned individuals, but never more so than in the wake of the Global Financial Crisis. Working as an economist for various financial institutions for more than twenty-five years Russell Jones had a foot in both camps. He plied his trade in a number of global financial centres - including London, Tokyo, Sydney, New York and Abu Dhabi - experiencing at first hand the extraordinary ebb and flow of an industry that came to exert a disproportionate influence on the lives of almost everyone on the planet. This is the story of his journey.